Prevalence and detection of drug resistant mutations in Mycobacterium tuberculosis among drug naïve patients in Nairobi, Kenya - Ogari, Collins Otieno (BMC Infect Dis, 2019)
BACKGROUND: Tuberculosis (TB), an ancient scourge of humanity known for several thousands of years, is still a significant public health challenge in many countries today even though some progress has been made in recent years in controlling the disease. The study’s aim was to determine the prevalence of mutations responsible for drug resistance in Mycobacterium tuberculosis among patients visiting selected health centers in Nairobi, Kenya. METHODS: The cross-sectional study involved 132 TB positive patients visiting Mbagathi and Chandaria hospitals between September 2015 and August 2016. Sputum samples were collected from the participants and handled in a biosafety level 3 laboratory at the Kenya Medical Research Institute (KEMRI). Samples were decontaminated using N-Acetyl-L-Cysteine (NALC) – Sodium Hydroxide (NALC-NaOH), stained using Zeihl–Neelsen (ZN), and cultured in Mycobacterium Growth Indicator Tube (MGIT). DNA extracted from cultured isolates using Genolyse™ technique was subjected to Multiplex PCR amplification and reverse hybridization for detection of drug resistance mutations on rpoB, katG, inhA, gyrA, gyrB, rrs and eis genes using Hain Genotype MTBDRplus and MTBDRsl. RESULTS: All 132 (100%) patients included in the study were culture positive for M. tuberculosis. Among them, 72 (54%) were male while the remaining 60 (46%) were female. The mean age of the patients was 26.4 ± 19.4 (SD) with a range of 18 to 60 years. Overall, the prevalence of the resistance to first and second-line TB drugs was 1.5% (2/132). Resistance to isoniazid (INH) was observed in 1 of 132 patients (0.8%), as was multi-drug resistant tuberculosis (MDR-TB), also at 0.8%. No resistance to fluoroquinolones (FQ) or kanamycin (KAN) was observed. The INH resistant strain had the katG mutations S315 T, while mutations detected for the MDR-TB were katG S513 T for INH, rpoB S531 L for rifampicin (RIF) and rrs G1484 T for cross-resistance to aminoglycosides/capreomycin (AG/CP). CONCLUSIONS: Molecular analysis confirms transmission of the drug-resistant M. tuberculosis strains. The data suggested that there is homogeneity when it comes to the type of drug resistance and mutation that occurs in the region. This calls for intensified drug resistance surveillance and drug adherence among patients infected with TB.